THE EXISTENCE OF INTEGRATED ISLAMIC EDUCATION IN MALAYSIA - Maimun Aqsha Lubis; Budi Sanjaya (Postgraduate Studies UIN Sulthan Thaha Saifuddin Jambi, 2022)
The Philosophy of Integrated Education covers the whole of the sciences between religious sciences and world sciences. Simply put, integrated education means education that integrates the knowledge of fardhu ain and kifayah. Integrating Islamic education also means integrating useful knowledge or aqli knowledge with naqli knowledge. Integrated education aims to form a moral balance and spiritual development to achieve knowledge, which is an integrated goal in the pursuit of knowledge. Meanwhile, the practice of integrated education from a pedagogical point of view is based on four elements, namely creativity, reflectivity, reciprocity and responsibility. All elements support the integration of knowledge and practice in terms of innovation and in line with current technological advances. The progress and change of Islamic education in Malaysia in accordance with the philosophical principles and policies are set by the Ministry of Education Malaysia based on the National Philosophy of Education and the Philosophy of Islamic Education. The methodology of this study is in the form of literature and direct observation (involved). This article aims to explain integrated education from the point of view of educational philosophy, integrated education from the point of pedagogy, and the existence of integrated education and its challenges in Malaysia. The existence of integrated Islamic education in Malaysia based on the National Philosophy of Education and the Philosophy of Islamic Education to form and apply Islamic or pure values ​​guided by al-Quran and al-Sunnah in integrating knowledge has recently emerged challenged its integration with critical, creative, and innovative thinking practices. Abstrak: Filsafat Pendidikan Terpadu mencakup keseluruhan ilmu antara ilmu-ilmu agama dan ilmu-ilmu dunia. Secara sederhana, pendidikan terpadu berarti pendidikan yang memadukan ilmu fardhu ain dan kifayah. Mengintegrasikan pendidikan Islam juga berarti memadukan ilmu yang bermanfaat atau ilmu aqli dengan ilmu naqli. Pendidikan terpadu bertujuan untuk membentuk keseimbangan moral dan perkembangan spiritual untuk mencapai ilmu pengetahuan, yang merupakan tujuan terpadu dalam mengejar ilmu pengetahuan. Sementara itu, praktik pendidikan terpadu dari sudut pandang pedagogis didasarkan pada empat unsur, yaitu kreativitas, reflektifitas, timbal balik, dan tanggung jawab. Semua elemen tersebut mendukung integrasi pengetahuan dan praktik dalam hal inovasi dan sejalan dengan kemajuan teknologi saat ini. Kemajuan dan perubahan pendidikan Islam di Malaysia sesuai dengan prinsip dan kebijakan filosofis yang ditetapkan oleh Kementerian Pendidikan Malaysia berdasarkan pada Filsafat Pendidikan Nasional dan Filsafat Pendidikan Islam. Metodologi penelitian ini berupa studi pustaka dan observasi langsung (terlibat). Artikel ini bertujuan untuk menjelaskan pendidikan terpadu dari sudut pandang filsafat pendidikan, pendidikan terpadu dari sudut pedagogi dan keberadaan pendidikan terpadu dan tantangannya di Malaysia. Dengan demikian, keberadaan pendidikan Islam terpadu di Malaysia berdasarkan Filsafat Pendidikan Nasional dan Filsafat Pendidikan Islam untuk membentuk dan menerapkan nilai-nilai Islam/murni yang berpedoman pada al-Quran dan al-Sunnah dalam mengintegrasikan ilmu pengetahuan akhir-akhir ini muncul tantangannya. integrasi dengan praktik berpikir kritis, kreatif dan inovatif. Kata-kata kunci: filsafat pendidikan Islam terpadu, unsur pendidikan Islam terpadu, pengetahuan